FUZZY ALGORITHM FOR ADAPTIVE IMAGE CONTRAST INCREASING НЕЧЕТКИЙ АЛГОРИТМ АДАПТИВНОГО ПОВЫШЕНИЯ КОНТРАСТОВ ИЗОБРАЖЕНИЙ - et. al., D. T. Muhamadiyeva, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A fuzzy algorithm for adaptive enhancement of image contrasts is considered, which is a characteristic of how wide the spread of the colors of image pixels is. The greater the spread of the pixel color values, the greater the contrast of the image. The main disadvantages of images, in most cases, are distorted brightness characteristics and low contrast. Therefore, the work is devoted to improving the contrasts of the image and converting the image to this form, which makes them more contrasting and, accordingly, more informative.